The Allium Genomes (Compendium of Plant Genomes, 2018)
This book describes the latest advances in Allium genome research. Allium includes plant species known for their huge nuclear genome size, which makes them ideal for somatic chromosome observations in high school experiments. In order to advance the genome analysis of A. cepa and its functional study, scientists in international research collaborations have developed several types of artificially manipulated genetic stocks and analyzed them using modern technologies. The Allium vegetable crop includes garlic, shallot, wakegi onion, Japanese bunching onion, and rakkyo. Bulb onion is one of the world's most important Allium commercial crops, with an estimated annual production of 85.8 million tons in 2013, and ranking third after tomato and watermelon in terms of global vegetable crops.